Strong immune responses and robust protection following a novel protein in adjuvant tuberculosis vaccine candidate - Marcellus Korompis; Christopher J De Voss; Shuailin Li; Alexandre Richard; Salem Salman Almujri; Alberta Ateere; Géraldine Frank; Céline Lemoine; Helen McShane; Elena Stylianou (Scientific Reports)
Abstract BCG remains the only licensed vaccine for tuberculosis (TB), but its efficacy wanes over time. Subunit vaccines, aim to improve BCG immunity and protection, by inducing responses to a few mycobacterial antigens delivered with a specific platform. Since the platform shapes the immune response induced, selecting the right platform has been challenging due to the lack of immune correlates of protection. Recently, the protein-adjuvated subunit vaccine. M72/AS01E, demonstrated 49.7% efficacy in preventing active TB in latently infected adults, indicating that protective immunity through subunit vaccines is possible. In this study we evaluated the immunogenicity and efficacy of the promising mycobacterial antigen PPE15, formulated with five adjuvants developed by the Vaccine Formulation Institute. While all adjuvants were immunogenic, PPE15 with LMQ protected vaccinated mice against an in vivo Mycobacterium tuberculosis challenge, both as a standalone vaccine and as a boost to BCG. Vaccinated mice had enriched lung parenchymal antigen-specific CD4 + CXCR3 + KLRG1− T cells previously associated with TB protection. Heterologous vaccination strategies were also explored by combining intranasal ChAdOx1.PPE15 viral vector, with intramuscular PPE15-LMQ resulting in improved protection compared to individual vaccines. These findings support the progression of this vaccine candidate to the next stages of development.